STRYV365 peak team and Brain agents: teacher perspectives on school impact of a trauma-informed, social–emotional learning approach for students facing adverse childhood experiences - Stoltenburg, Abbey; McGuire, Madison; Liverman, Elizabeth; Lumelsky, Paula; Bates, Garrett; Gundacker, Constance; Currie, Brandon; Meurer, John R. (Frontiers in Psychology, 2024)
Adverse childhood experiences (ACEs) have significant impacts on child and adolescent school performance and overall wellbeing, while positive childhood experiences limit the impact of ACEs on wellbeing and health. Trauma-informed and social emotional learning (SEL) programming in schools may address the impacts of ACEs and school staff are critical to the success of these programs and school outcomes. The aim of this study was to determine strengths, weaknesses, and opportunities for improvement of STRYV365 peak team and Brain Agents programs to refine implementation and determine the preliminary impacts on students, teachers, and school environments at participating schools. Four focus groups were conducted after programming concluded with 17 school leaders, administrators, and teachers at four urban schools with programs for fifth to ninth grade students. Audio transcripts were obtained from a professional transcribing service. Four co-authors coded major themes and subthemes by inductive analysis using Dedoose. Three major themes were identified from transcripts: schoolwide perspectives of STRYV365 programs, strengths and impacts of STRVY365 programs, and opportunities for program improvement. School staff reported peak team was engaging for students and helped students learn SEL skills and form peer-to-coach and peer-to-peer connections. STRYV365 programs also positively impacted student-teacher relationships and staff relationships. Teachers overwhelmingly indicated interest in becoming more involved in future programming. Overall, this study highlights the importance of teacher and administrator support for SEL activities, consistency for urban youth, and suggests that 4-week SEL programs may have a positive impact on school culture, student-teacher relationships, and teacher-teacher relationships.